2003
DOI: 10.1123/pes.15.3.243
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity and Cognition in Children: A Meta-Analysis

Abstract: The purpose of this study was to quantitatively combine and examine the results of studies pertaining to physical activity and cognition in children. Studies meeting the inclusion criteria were coded based on design and descriptive characteristics, subject characteristics, activity characteristics, and cognitive assessment method. Effect sizes (ESs) were calculated for each study and an overall ES and average ESs relative to moderator variables were then calculated. ESs (n = 125) from 44 studies were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
743
5
49

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 973 publications
(832 citation statements)
references
References 18 publications
35
743
5
49
Order By: Relevance
“…The findings of the present study, that only word reading scores were significantly different between rest and exercise, matches similar studies using the WrAT test exercise that found improved reading comprehension but not spelling or arithmetic [8] or improved spelling and reading scores [10]. These positive benefits could be attributed to the cognitive benefits resulting from physical activity [1,2] particularly immediate and delayed recall [11]. The results also support those of [8,10] in that acute bouts of class based exercise have an adverse effect on arithmetic.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The findings of the present study, that only word reading scores were significantly different between rest and exercise, matches similar studies using the WrAT test exercise that found improved reading comprehension but not spelling or arithmetic [8] or improved spelling and reading scores [10]. These positive benefits could be attributed to the cognitive benefits resulting from physical activity [1,2] particularly immediate and delayed recall [11]. The results also support those of [8,10] in that acute bouts of class based exercise have an adverse effect on arithmetic.…”
Section: Discussionsupporting
confidence: 77%
“…research has shown acute exercise to have beneficial effects on cognition and subsequently academic achievement. It has been suggested that children gain cognitive benefits from physical activity [1,2] with greatest improvements seen in complex mental processing [3]. Standardised achievement in maths and reading [4] as well as increased performance in core academic classes has been reported for children who participate in vigorous physical activity outside of school [5].…”
Section: Introductionmentioning
confidence: 99%
“…Emphasis on educational attainment in childhood as a barrier to PA is a recurrent theme in research with particular ethnic minority groups (e.g., Chinese [48], Middle Eastern [11], Bangladeshi, Pakistani and Black African [17] populations) living in Western countries. Given parental concern about education, relating the benefits of PA to improved concentration and cognitive functioning [49,50] may increase engagement in activities.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that fitter and more active children showed a range of physiological benefits (e.g., greater grey matter volume in the hippocampus, more effective brain activity patterns), performed better on tasks that require executive control and associative memory, and showed higher academic achievement. There is extensive research supporting the finding that physical activity positively correlates to cognitive performance (for reviews, see Barenberg, Berse, & Dutke, 2011;Erickson et al, 2015;Fedewa & Ahn, 2011;Sibley & Etnier, 2003;Tomporowski, Davis, Miller, & Naglieri, 2008). It has become clear from those studies that the type of activity, level of intensity, duration of exercise required, aspects of cognition, and learner characteristics affect the relationship between physical activity and cognitive performance.…”
Section: Effects Of Whole-body Movementsmentioning
confidence: 99%